2019
DOI: 10.1177/0023830919866225
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic Category Formation is Perceptually Driven During the Early Stages of Adult L2 Development

Abstract: Research on the acquisition of L2 phonology in sequential language learners has stressed the importance of language use and input as a means to accurate production and perception; however, the two constructs are difficult to evaluate and control. This study focuses on the role of language use during the initial stages of development of phonetic categories related to stop voicing and analyzes the relationship between production and perception. Native English-speaking late learners of Spanish provided production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 56 publications
4
21
0
Order By: Relevance
“…The fact that the between‐subjects but not within‐subjects perception predictors were significantly related to production in the current study intersects with previous research showing significant positive correlations when perception and production are sampled cross‐sectionally (e.g., Evans & Alshangiti, 2018; Flege et al., 1999; Saito & van Poeteren, 2017) but varying degrees of alignment when the two modalities are sampled longitudinally (Casillas, 2020a; Hanulíková et al., 2012; Kartushina et al., 2015; Nagle, 2018). Given the growing body of work on the topic, there seems to be an emerging consensus that “accurate L2 speech perception is not sufficient for accurate L2 speech production” (Kartushina et al., 2015, p. 828) or that the relationship between the two modalities is at least more complex and time‐sensitive (e.g., Nagle, 2018) than current theory would suggest.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The fact that the between‐subjects but not within‐subjects perception predictors were significantly related to production in the current study intersects with previous research showing significant positive correlations when perception and production are sampled cross‐sectionally (e.g., Evans & Alshangiti, 2018; Flege et al., 1999; Saito & van Poeteren, 2017) but varying degrees of alignment when the two modalities are sampled longitudinally (Casillas, 2020a; Hanulíková et al., 2012; Kartushina et al., 2015; Nagle, 2018). Given the growing body of work on the topic, there seems to be an emerging consensus that “accurate L2 speech perception is not sufficient for accurate L2 speech production” (Kartushina et al., 2015, p. 828) or that the relationship between the two modalities is at least more complex and time‐sensitive (e.g., Nagle, 2018) than current theory would suggest.…”
Section: Discussionsupporting
confidence: 88%
“…Given that the speech learning model (Flege, 1995) hypothesizes that listeners must discriminate similar sounds before they can create a new phonetic category in the L2, an identification task, where listeners must associate an auditory stimulus with a category label, may be a more appropriate measure of perceptual learning (i.e., category formation) than the categorial discrimination task used in this study. Along the same lines, other approaches to operationalizing perception and production accuracy, such as through the use of crossover boundaries (Casillas, 2020a), may prove beneficial. Simply put, until a larger body of longitudinal studies has been accumulated, definitive conclusions about the time‐varying nature of the perception–production link cannot be reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a weak correlation could signal a lagged relationship, in which case cross-lagged measures would show a stronger relationship than their time-locked counterparts. To that point, longitudinal developmental studies-studies that observed perception-production relationships over time without providing training in either modality-point to a lagged model (Casillas, 2020a(Casillas, , 2020bNagle, 2018).…”
Section: Developmental Stagementioning
confidence: 99%
“…Listeners heard each stimulus and were asked to classify it using a closed set of options. Similar tasks have been used to evaluate L2 listeners' reliance on spectral and duration cues in the perception of L2 vowel contrasts (e.g., Flege et al, 1997;Sakai, 2016) and to gain insight into the precise location of L2 phonemic boundaries, including how such boundaries change over time as a function of L2 experience (e.g., Casillas, 2020b).…”
Section: Measuring Perceptionmentioning
confidence: 99%